Тӧдьы юсьёс берто: кылбуръёс / Михаил Федотов - Федотов Михаил Иванович (Удмуртия, 1986)
Экземпляры: ф.2 (1986) / Инвентарный номер: 11863 / Цена: 0.25 / Авт.знак: Ф 34 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)